The Impact of Glass Ceiling: Prospects For Women's Career Development in Bureaucracy and The Performance of Public Sector Organizations - I Gede Eko Putra Sri Sentanu (Sekolah Pascasarjana Universitas Brawijaya, 2019)
This study examines the practice of responsive and gender-friendly policies to encourage women's career prospects in the bureaucratic structure to improve the performance of local government agencies of the Malang City Government. The theoretical approach used is Glass Ceiling, to explain the strategic position of women, especially related to the barrier factor of women in achieving the highest position in an organization. The purpose of this study was to analyze the effect of the relationship between the glass ceiling on women's career development in bureaucracy. This study uses a quantitative approach, namely explanatory research to answer the questions in this study with quantitative and qualitative analysis. The sample in this study was all of the Government agencies in Malang City which amounted to 43 units with 126 respondents. The quantitative analysis used was Partial Least Square (PLS) -SEM. The results of this study indicate that there is an influence between the Glass Ceiling on women's career development and the performance of local government agencies in Malang City Government.